A risk factor analysis of accumulated postoperative pain and swelling sensation after dental implant surgery using a cellular phone-based real-time assessment - Kuroi, Ryuta; Minakuchi, Hajime; Hara, Emilio Satoshi; Kawakami, Aya; Maekawa, Kenji; Okada, Hiroki; Kuboki, Takuo (Journal of prosthodontic research, 2015)
The purpose of this study was to identify the related risk factors of dental implant accumulated postoperative pain and swelling by cellular phone-based assessment. Subjects were a consecutive series of patients who received oral implant surgery at Okayama University Hospital. Cellular phone-based questionnaire was sent at pre-set schedule to each subject every 2h on the day of surgery, and every 24h from the 2nd to 7th day post-surgery. Subjects replied in real-time the pain and swelling levels at the operated sites by an 11- and 4-grade rating-scale questionnaire. Overall intensity of individual pain and swelling was calculated by means of area under curve that drew by their time-dependent changes. Predictor variables were age, gender, presence of diabetes mellitus and/or hypertension (DM/HT), history of implant surgery, number of inserted implants, flap operation, surgical duration, pre-surgery anxiety, osteoplasty, bone quality, premedication, dosage of prescribed analgesics and local anesthesia and accumulated postoperative pain/swelling. Compliance rate and risk factors correlated with accumulated postoperative pain and swelling were calculated by multiple regression analysis. Final subjects were 18 females and 7 male (mean age: 59.3±7.32 yrs). Significant factors correlated with accumulated postoperative pain were DM/HT, surgical duration, premedication, bone quality, pre-surgery anxiety and postoperative swelling (R2=0.769, p=0.001, 0.013, 0.032, 0.007, 0.035 and 0.007, respectively). Meanwhile, significant factors associated with postoperative swelling were postoperative pain, DM/HT and bone quality (R2=0.365, p=0.002, 0.004, 0.008, respectively). These results suggested DM/HT and bone quality are correlated to overall intensity of postoperative pain and swelling.